Storing use case descriptions in the relational database - Mateljan, Vladimir (Array, 2011)
Many authors perceive the use case description as structured text consisting of several mandatory elements. We can store use case descriptions in separate files, but there are problems with searching and organizing these files and their elements into categories. These elements of the use case description might be stored in the relational database and later efficiently retrieved or categorized just in time. This paper proposes database schema for the relational database of use case descriptions and provides some database queries.